A 2000-year record of lake ontogeny and climate variability from the north-eastern European Russian Arctic. (March 2017) - Luoto, Tomi P; Kuhry, Peter; Holzkämper, Steffen; Solovieva, Nadia; Self, Angela E
A lake sediment record from the north-eastern European Russian Arctic was examined using palaeolimnological methods, including subfossil chironomid and diatom analysis. The objective of this study is to disentangle environmental history of the lake and climate variability during the past 2000 years. The sediment profile was divided into two main sections following changes in the lithology, separating the limno-telmatic phase between 2000 and 1200 cal. yr BP and the lacustrine phase between 1200 cal. yr BP and the present. Owing to the large proportion of semi-terrestrial chironomids and poor modern analogues, a reliable chironomid-based temperature reconstruction for the limno-telmatic phase was not possible. However, the lacustrine phase showed gradually cooling climate conditions from 1200 cal. yr BP until 700 cal. yr BP. The increase in stream chironomids within this sediment section indicates that this period may also have had increased precipitation that caused the adjacent river to overflow, subsequently transporting chironomids to the lacustrine basin. After a short-lived warm phase at 700 cal. yr BP, the climate again cooled, and a progressive climate warming trend was evident from the most recent sediment samples, where the biological assemblages seem to have experienced an eutrophication-like response to climate warming. The temperature reconstruction showed more similarities with the climate development in the Siberian side of the Urals than with northern Europe. This study provides a characteristic archive of arctic lake ontogeny and a valuable temperature record from a remote climate-sensitive area of northern Russia.